The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1042/bj2610301
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an arginine residue at the coenzyme-binding site of Escherichia coli isocitrate dehydrogenase

Abstract: The arginine-specific reagent phenylglyoxal inactivated the active, dephosphorylated, form of Escherichia coli isocitrate dehydrogenase rapidly in a pseudo-first-order process. Both NADP+ and NADPH protected the enzyme against inactivation. Phenylglyoxal appeared to react with one arginine residue per subunit, and the extent of the reaction was proportional to the extent of the inactivation. In contrast, the phosphorylated form of isocitrate dehydrogenase did not react detectably with phenylglyoxal. The data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The phenylglyoxal-arginine product formed in Ap4A phosphorylase I is unstable under the conditions required for amino acid analysis and isolation of phenylglyoxal-labelled peptides. Similar instability of phenylglyoxal-arginine products in other enzymes has been reported (Jornvall et al, 1977;McKee & Nimmo, 1989). However, the stability of the inactivated enzyme to high dilution, precipitation with trichloroacetic acid and dissociation in SDS support the kinetic data that phenylglyoxal acts as an irreversible inhibitor of Ap4A phosphorylase I.…”
Section: Discussionsupporting
confidence: 83%
“…The phenylglyoxal-arginine product formed in Ap4A phosphorylase I is unstable under the conditions required for amino acid analysis and isolation of phenylglyoxal-labelled peptides. Similar instability of phenylglyoxal-arginine products in other enzymes has been reported (Jornvall et al, 1977;McKee & Nimmo, 1989). However, the stability of the inactivated enzyme to high dilution, precipitation with trichloroacetic acid and dissociation in SDS support the kinetic data that phenylglyoxal acts as an irreversible inhibitor of Ap4A phosphorylase I.…”
Section: Discussionsupporting
confidence: 83%
“…Earlier studies with model compounds found that the stoichiometry of the reaction of phenylglyoxal with arginine requires 2 mol of phenylglyoxal for each molar equivalent of arginine residue (Takahashi, 1968;Lange et al, 1974;Cheng & Nowak, 1989). However, examples are also known where a 1:1 stoichiometry was found, depending on the particular local conformation of the enzyme active site (Borders & Riordan, 1975;Gildensoph & Briskin, 1989;McKee & Nimmo, 1989). In any event, it appears that at least one arginine is essential for BHPTP activity.…”
Section: Resultsmentioning
confidence: 99%
“…9). The activity of ICD also regulates the flux split between the full TCA cycle and the glyoxylate shunt (49)(50)(51). A point mutation at residue 395 that changed the amino acid from positively charged (L-arginine) to negatively charged (L-cysteine) in ICD was found in all ePgi replicates except replicate 7 (Fig.…”
Section: Resultsmentioning
confidence: 99%